Status of women at the competitiveness of today in the kazakh modern society (Journal of Philosophy Culture and Political Science, 2018)
This article is about the way which Kazakh woman should follow to prosper her society. Now unfortunately with all good things which come from Western countries such as technology, education and so on, we are blindly following to the western woman’s behavior which is not acceptable for Kazakh woman as Muslim woman. Because we see that western woman became even higher than man because of radical feminism which is not productive for future of society, especially when we talk about fertility. We need to explain to Kazakh woman that Koran has various interpretations given in different times. The most important thing is we have to identify the requirements of our time according to Islam and follow not to the letters of Koran but to the meaning of Koran. Only traditions which make future better should survive, otherwise people never prosper. We have to question our traditions and measure them with Koran and Sunnah. Muslim scientists questioned every aspect of their lives and understood the first word of Allah «ikra» positively, so they really read everything with big interest. I try to show to Kazakh woman that Islam never consider woman only as mother or only as wife and never stops your personal development but encourage it. Women can’t just stay behind man in shadow without having her own opinion, because Koran teach as that we are responsible for our life, so women shouldn’t just follow her husband but she has to be a person who aware of her responsibilities. Key words: Islam, women’s status, women in Koran, feminism, primitiveness, spiritual value, happiness, family, Kazakhstan.